Collapse prevention of pre-stressed electric transmission poles using glass fiber reinforced polymers - Rattapoohm Parichatprecha; Kittipoom Rodsin; Songsak Suthasupradit; Tahir Mehmood; Adnan Nawaz (Case Studies in Construction Materials)
Natural hazards such as strong winds, typhoons, and earthquakes have caused massive economic losses in the form of damage to residential and life-line structures. Electric transmission infrastructures are life-line structures susceptible to severe damage under lateral loads like wind and earthquakes. This study focused on vulnerability assessment and measures to reduce the expected damage to the prestressed electric transmission poles under lateral loads. The Glass Fiber Reinforced Polymer (GFRP) sheet is selected as a strengthening material because the fiber cost is affordable but still has acceptable high tensile strength. A full-scale 12-meter-long prestressed transmission pole was tested under reversed cyclic lateral loading. Furthermore, another specimen strengthened with the GFRP sheet was tested to quantify the effectiveness of this technique. The experimental results show significant improvement in the lateral response behavior of prestressed poles in terms of lateral drift capacity, ductility, and energy dissipation characteristics. The GFRP-strengthened specimen exhibited a significantly enhanced lateral drift capacity (more than 100 %) compared to the control specimen. The performance of GFRP in preventing the collapse of a full-scale transmission pole is proved experimentally in this study. Finally, a numerical model based on the fiber modeling concept was also implemented in the open-source platform OpenSees to simulate the observed hysteretic behavior for strengthened and unstrengthened prestressed electric transmission poles. The application of this strengthening method is shown to be very practical for collapse prevention of existing PC poles both in terms of performance and budget.